Merdeka Curriculum Learning Strategy in Effort Building Student Potential - Sulaiman W; Muhammad Nur; Sulaiman Ismail (Yayasan Adra Karima Hubbi, 2024)
Background. Learning strategies in the independent curriculum must be optimized for teachers as the spearhead in advancing mutually beneficial education. If this is not realized, then the government's hopes of overcoming the weaknesses of Indonesian education will not be realized. This benchmark is the reference for researchers to describe how the Merdeka Curriculum learning strategies are used to build student potential. Purpose. This qualitative research describes how the Merdeka Curriculum learning strategies build student potential. Method. This study refers to